The Future of Instruction Media in Indonesian Education: Systematic Review - Sudarmo Sudarmo; Ardian Arifin; Petrus Jacob Pattiasina; Vani Wirawan; Aslan Aslan (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aimed to answer whether digital devices replace print media in education in Indonesia's digital era. Systematic studies and experts' findings can get a basic understanding of print media that can be replaced by digital media in education today and in the future. For this reason, the researchers have attempted to collect literature and publications related to this theme. Then it analyzes critically to prove whether our hypothesis is accepted or rejected. For example, the way we research seeks to understand the question's theme and matches the findings of several publications that we target from 2010 to 2020. Data sources come from Google Scholar, ERIC publications, and other search engines. This analytical process involves coding systems, content evaluation, in-depth interpretation, and concluding to obtain findings characterized by validity and trustworthiness. The results reveal that slowly the role of electronic media has begun to take over paper media. However, with the condition of Indonesian education in general, the role of print media continues to dominate the world of Indonesian education today, especially in remote areas of the country where modern educational facilities are not yet supported. Therefore, this finding is useful for policymakers and further study in a similar field.